Emergency Intracranial Stenting in Acute Stroke: Predictors for Poor Outcome and for Complications. Issue 5 (3rd March 2020) - Stracke, Christian Paul; Fiehler, Jens; Meyer, Lukas; Thomalla, Götz; Krause, Lars Udo; Lowens, Stephan; Rothaupt, Jan; Kim, Byung Moon; Heo, Ji Hoe; Yeo, Leonard L.L.; Andersson, Tommy; Kabbasch, Christoph; et al.
Abstract : Background: Stent‐retriever thrombectomy is the first‐line therapy in acute stroke with intracranial large vessel occlusion. In case of failure of stent‐retriever thrombectomy, rescue stent angioplasty might be the only treatment option to achieve permanent recanalization. This study aims at identifying predictors for poor outcome and complications in a large, multicenter cohort receiving rescue stent angioplasty. Methods and Results: We performed a retrospective analysis of patients with large vessel occlusion who were treated with rescue stent angioplasty after stent‐retriever thrombectomy between 2012 and 2018 in 7 neurovascular centers. We defined 2 binary outcomes: (1) functional clinical outcome (good modified Rankin Scale, 0–2; and poor modified Rankin Scale, 4–6) and (2) early symptomatic intracerebral hemorrhage. Impacts of clinical, radiological, and interventional parameters on outcomewere assessed in uni‐ and multivariable logistic regression models. Two hundred ten patients were included with target vessels located within the anterior circulation (136 of 210; 64.8%) and posterior circulation (74 of 210; 35.2%). Symptomatic intracerebral hemorrhage occured in 22 patients, 86.4% (19 of 22) after anterior and 13.6% (3 of 22) after posterior circulation large vessel occlusion. Good functional outcome was observed in 44.8% (73 of 163). A higher National Institutes of Health Stroke Scale on admission (adjusted odds ratio, 1.10; P= 0.002), a higher premorbid modified Rankin Scale (adjusted odds ratio, 2.02; P =0.049), and a modified Thrombolysis in Cerebral Infarction score of 0 to 2a after stenting (adjusted odds ratio, 23.24; P <0.001) were independent predictors of poor functional outcome. Conclusions: Use of rescue stent angioplasty can be considered for acute intracranial large vessel occlusion in cases after unsuccessful stent‐retriever thrombectomy. Likelihood of symptomatic intracerebral hemorrhage is higher in anterior circulation stroke.